Inflammatory profile of patients with different weight diagnoses and similar periodontal condition: A systematic review - Juliana dos Santos Feijo; Ana Flávia Leite Pontes; Taciane Menezes da Silveira; Natália Marcumini Pola; Francisco Wilker Mustafa Gomes Muniz (Wolters Kluwer Medknow Publications, 2024)
Background: This study aimed to systematically review the literature regarding the inflammatory profiles, measured by cytokines and chemokines, of individuals with different diagnoses of weight, but with the similar periodontal condition. Materials and Methods: Searches were performed in five databases (Scopus, EMBASE, PubMed, Web of Science, and Cochrane-Central). Studies that compared the inflammatory profile of normal-weight individuals to those with obesity and evaluated the same cytokine, collection method, and periodontal diagnosis (periodontal health, gingivitis, or periodontitis) were included. Cross-sectional studies underwent evaluation by independent researchers using the Joanna Briggs Institute Critical Appraisal Checklist. The GRADE (Grades of Recommendation, Assessment, Development and Evaluation) system assessed evidence certainty. Results: Twelve studies were included. The diagnosis of obesity was done on the basis of body mass index, waist circumference, and waist-hip ratio. Pro-inflammatory cytokines (interleukin-6 [IL-6], tumor necrosis factor-α [TNF]-α, IL-1β, IL-31, and IL-34) were analyzed in serum, saliva, gingival crevicular fluid (GCF), and plasma. Periodontal diagnoses varied across studies. TNF-α expression was significantly higher in individuals with obesity and periodontal health or periodontitis. Serum IL-1β levels showed mixed results, but salivary IL-1β levels were elevated in obese individuals. IL-6 levels were higher in obese individuals, regardless of periodontal status. IL-34 and IL-10 showed no significant differences across groups. Monocyte chemoattractant protein-4 (MCP-4) levels were higher in obese individuals with periodontitis or periodontal health. IL-31 and IL-34 in GCF showed no significant differences between obese and nonobese individuals, without periodontitis. Conclusions: Heterogeneous results were noted for IL-6, IL-1β, IL-31, IL-34, TNF-α, and MCP-4, hindering conclusions on weight's impact on inflammatory profiles in periodontal patients.